An Investigation of Descending Pain Modulation in Women With Provoked Vestibulodynia: Alterations of Brain Connectivity - Yessick, Lindsey R.; Pukall, Caroline F.; Ioachim, Gabriela; Chamberlain, Susan M.; Stroman, Patrick W. (Frontiers in Pain Research, 2021)
Provoked Vestibulodynia (PVD) is the most common vulvodynia subtype (idiopathic chronic vulvar pain). Functional magnetic resonance imaging (fMRI) studies indicate that women with PVD exhibit altered function in a number of pain modulatory regions in response to noxious stimulation, such as in the secondary somatosensory cortex, insula, dorsal midcingulate, posterior cingulate, and thalamus. However, previous neuroimaging studies of PVD have not examined periods of time before and after noxious stimulation or investigated functional connectivity among pain modulatory regions. Fourteen women with PVD and fourteen matched Control participants underwent five fMRI runs with no painful stimuli interleaved randomly with five runs with calibrated, moderately painful heat stimuli. As recent findings indicate that pain processing begins before and continues after painful stimulation, two-minute periods were included in each run before and after the stimulus. Functional brain connectivity was assessed during both trials of Pain and No Pain stimulation for each group using structural equation modeling (SEM). Analyses of variance (ANOVAs) on connectivity values demonstrated significant main effects of study condition, and group, for connectivity among pain modulatory regions. Most of the differences between the Pain and No Pain conditions found only in the PVD group take place before (i.e., thalamus to INS, ACC to S1, thalamus to S1, and thalamus to S2) and after pain stimulation (i.e., INS to amygdala, PPC to S1, and thalamus to S2). Such differences were not observed in the Control group. These findings further support previous results indicating that women with PVD have altered pain processing compared to pain-free women.